2017
DOI: 10.5586/asbp.3562
|View full text |Cite
|
Sign up to set email alerts
|

Do local enemies attack alien and native Impatiens alike?

Abstract: The enemy release hypothesis (ERH) attributes the invasive behavior of some alien species to decreased pressure from natural enemies, as they have been left behind in the hosts' native range. The majority of research supports this idea, but some studies confirm it only partially or even contradict it. Here, we present the results of ERH tests of three Impatiens species studied in southern Poland in 2010-2011. Two of them are alien and invasive in Europe (Impatiens glandulifera, I. parviflora) and one is native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…We selected this plant group because it is a species-rich group with many species co-occurring in similar habitats along wide altitudinal ranges with a strong temperature gradient 24 . In addition, the interactions of several species from the genus Impatiens with herbivores have been previously intensively studied 25,26 . For example, Gruntman et al 25 recorded resistance to the generalist herbivore coupled with production of specific secondary defence compounds at I. glandulifera.…”
Section: Methodsmentioning
confidence: 99%
“…We selected this plant group because it is a species-rich group with many species co-occurring in similar habitats along wide altitudinal ranges with a strong temperature gradient 24 . In addition, the interactions of several species from the genus Impatiens with herbivores have been previously intensively studied 25,26 . For example, Gruntman et al 25 recorded resistance to the generalist herbivore coupled with production of specific secondary defence compounds at I. glandulifera.…”
Section: Methodsmentioning
confidence: 99%
“…glandulifera experiences much lower levels of leaf damage by natural pests and invertebrate herbivory in invasive UK populations (<15% of leaves damaged) than in native Indian populations (up to 65% of leaves damaged) (Tanner et al, 2008(Tanner et al, , 2014b. Recent field studies in Poland, however, found similar levels of herbivore/pest damage of I. glandulifera leaves than of (native) I. noli-tangere leaves (Najberek et al, 2020a(Najberek et al, , 2017. The pressure of herbivores/pests varied across several Central European populations, with old populations (established 65-85 years ago) subject to higher levels of leaf damage and aphid pressure than recently established populations (5-25 years old) (Gruntman et al, 2017).…”
Section: Herbivores and Pathogensmentioning
confidence: 98%
“…in the Polish Tatra Mountains nonetheless showed that respectively 58% and 45% of leaves showed at least one disease or damage symptom. Observed symptoms included spots, necrosis, mines, discoloration, deformation, wilting and herbivory damage (Najberek et al, 2020a(Najberek et al, , 2017. Experimental work using fungicide and insecticide treatments suggest that generalist invertebrate herbivores and pests have little negative effects on I. glandulifera's fitness in Switzerland (Burkhart and Nentwig, 2008).…”
Section: Herbivores and Pathogensmentioning
confidence: 99%
“…Najberek et al (2017) provide evidence, that in the mountains in the Czech Republic, the invasive alien species I. glandulifera tended to be more attacked from pests than the native species Impatiens noli-tangere L. In another garden experiment by Kollmann et al (2007), for the first time a viral infection found by I. glandulifera in various European regions has been reported, which has led to reduce above-ground biomass of the invasive species. Based on the above statements, we tend to accept Najberek's (2017) claim, that the success of the ЕRH depends on various factors, the significance of which varies depending on the biotic and / or abiotic conditions of the place where the plant is introduced. The latter raises the question of establishing the role of local enemies on the Himalayan balsam populations in its invasion areas.…”
Section: Introductionmentioning
confidence: 85%